The Second Crusade and it's Contexts - Rec.: Jonathan Phillips. The Second Crusade. Extending the frontiers of Christendom. New Haven-London: Yale university press, 2007. 364 p. - Ščavinskas, Marius (Lietuvos istorijos studijos, 2010)
-
Keywords: -